Research on the Safety Thickness of Tunnel Outburst Prevention in Water-Rich Fault Fracture Zone Based on Janssen’s Theory - Zuliang Zhong; Yapeng Li; Xiaohan Zhou (Geofluids)
In the construction of tunnel in water-rich fault fracture zone, when the thickness of outburst prevention is insufficient, it is very easy to cause water and mud inrush engineering accident. Therefore, it is very necessary to study the safety thickness of outburst prevention for this type of tunnel. In this paper, the expression of in situ stress in water-rich fault fracture zone is derived based on Janssen’s theory. Two mechanical models of outburst prevention rock mass are established, and according to the shear balance theory, the calculation formula for the safe thickness of outburst prevention is determined and the parameter sensitivity analysis is carried out. Finally, it is verified by engineering examples and numerical simulation. The results show that: (1) the calculation formula of outburst prevention thickness proposed in this paper is more perfect and shows good prediction effect for deep- and shallow-buried tunnels; (2) the greater the angle α between tunnel axis and fault zone and the dip θ of fault fracture zone, the smaller the critical safety thickness of outburst prevention and the safer it is for tunnel construction; (3) when the fault fracture zone inclines inward relative to the tunnel face, the gravity of the rock mass in the fault zone will lead to an increase in the safety thickness of outburst prevention, and reinforcement measures should be taken during actual construction.